Rigless retargeting for character animation - SMITH JEFFREY D (2012)
Motion may be transferred between portions of two characters if those portions have a minimum topological similarity. The portions or structures of the source and target character topologies may be represented as one or more descriptive files comprised of a hierarchy of data objects including portion identifiers and functionality descriptors associated with portions of the respective source or target topology. To transfer motion between the source and target characters, the motion associated with the portions or structures of the source character identified by a subset of source portion identifiers having corresponding target portion identifiers is determined. This motion is retargeted to and attached to the corresponding portions or structures of the target character identifiers. As a result, the animation of the portions of the target character effectively animates the target character with motion that is similar to that of the source character.